2022
DOI: 10.3389/fninf.2022.1032636
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of brain nuclei in obese children with and without Prader-Willi syndrome

Abstract: Introduction: Prader-Willi syndrome (PWS) is a multisystem genetic imprinting disorder mainly characterized by hyperphagia and childhood obesity. Extensive structural alterations are expected in PWS patients, and their influence on brain nuclei should be early and profound. To date, few studies have investigated brain nuclei in children with PWS, although functional and structural alterations of the cortex have been reported widely.Methods: In the current study, we used T1-weighted magnetic resonance imaging t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 85 publications
0
9
0
Order By: Relevance
“…The volumes of components of the limbic system have been studied in numerous case-control studies in the context of different conditions in childhood including Prader–Willi syndrome [ 4 , 5 ], schizophrenia [ 11 , 12 , 16 , 18 ], bipolar disorder [ 13 ], depression [ 14 ], anxiety [ 31 ], autism spectrum disorder [ 32 , 33 ], attention deficit hyperactivity disorder [ 32 , 33 ], and children with obsessive-compulsive disorder [ 32 , 33 ]. However, normal values of the structures of the limbic system across the pediatric age range specific to sex and age are scarce.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The volumes of components of the limbic system have been studied in numerous case-control studies in the context of different conditions in childhood including Prader–Willi syndrome [ 4 , 5 ], schizophrenia [ 11 , 12 , 16 , 18 ], bipolar disorder [ 13 ], depression [ 14 ], anxiety [ 31 ], autism spectrum disorder [ 32 , 33 ], attention deficit hyperactivity disorder [ 32 , 33 ], and children with obsessive-compulsive disorder [ 32 , 33 ]. However, normal values of the structures of the limbic system across the pediatric age range specific to sex and age are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of the intricate structural and functional anatomy of the limbic system, its connectedness, and relationships to other brain regions is essential to better understand various disorders including schizophrenia, epilepsy, limbic encephalitis, dementia, anxiety disorders, and others [ 1 ]. Recently, Wu et al showed that automated volumetry of T1-weighted MR images can help elucidate the neuroanatomical correlate of Prader–Willi syndrome [ 4 ]. Prader–Willi syndrome is a genetic obesity disease characterized by an insatiable appetite, hyperphagia, and morbid to life-threatening obesity [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations